Simulados de abandono de área: sua importancia para escolas de educação infantil no Rio Grande do Sul - Chaves, Fábio Roberto (Universidade do Vale do Rio dos Sinos, 2017)
A series of requirements are required to comply with Rio Grande do Sul's legislation and obtain the Fire Protection and Prevention Permit (APPCI). Among these requests, for some occupations, is the emergency plan against fire and it contains the requirement simulated. The present work will deal with the importance of this simulation for kindergarten schools with an area of less than 750m² and a height of less than 12m. Who needs? What is its importance? Have the standards and technical instructions been elaborated in the light of emergency situations in these schools? We have private and municipal schools in the metropolitan region with over 100 children, including nursery classes, maternal, pre I, pre II. How are these schools prepared for emergencies? Would the number of employees be in agreement with the need for a quick and efficient evacuation? When you ring the emergency alarm siren, how would these children proceed? This work will present a case study of a kindergarten school in the municipality of Esteio that does not have an emergency plan, but that carried out a simulation of evacuation and registered the activity. And it includes some suggestions of improvements, in this context of prevention, that could be applied to this school of infantile education or others.
Keywords: Plano de emergência; Escolas de educação de infantil; Legislação no Rio Grande do Sul; Leis e decretos referentes às legislações de proteção e prevenção contra incêndio; Emergency plan; Schools of children's education; Legislation in Rio Grande do Sul; Laws and decrees referring to fire protection and prevention legislation